Dietary regimes and political regimes: the case of Italian fascism - Cervelli, Pierluigi (E|C, 2020)
The aim of this article is to investigate the relationships between food regimens and politics, starting from the case history of italian fascism. In details, the semiotic square of the system of values in the field of consumption (Floch 1990) will be used as a conceptual tool to understand a corpus of texts proposing food regimens and all belonging to the discoursive genre of the cookbook.